2020
DOI: 10.3390/ijms21217832
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Seizures and Purinergic Signalling

Abstract: Neonatal seizures are one of the most common comorbidities of neonatal encephalopathy, with seizures aggravating acute injury and clinical outcomes. Current treatment can control early life seizures; however, a high level of pharmacoresistance remains among infants, with increasing evidence suggesting current anti-seizure medication potentiating brain damage. This emphasises the need to develop safer therapeutic strategies with a different mechanism of action. The purinergic system, characterised by the use of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 303 publications
(378 reference statements)
0
4
0
Order By: Relevance
“…Therefore, the targeting of P2X 7 , thought to be mainly activated during pathological release of ATP, 201 may represent a promising novel treatment strategy for neonates. 202 Other studies, however, have shown only a moderate or no anticonvulsant effect of P2X 7 antagonism. Using the maximal electroshock seizurethreshold test and the Ptz (87 mg/kg, IP) seizure-threshold test in mice, Fischer et al showed no anticonvulsant effects provided by P2X 7 antagonism using four antagonists (JNJ47965567, AFC5128, BBG, and tanshinone IIA sulfonate).…”
Section: Targeting Of P2x Receptors During Seizures and Epilepsymentioning
confidence: 98%
“…Therefore, the targeting of P2X 7 , thought to be mainly activated during pathological release of ATP, 201 may represent a promising novel treatment strategy for neonates. 202 Other studies, however, have shown only a moderate or no anticonvulsant effect of P2X 7 antagonism. Using the maximal electroshock seizurethreshold test and the Ptz (87 mg/kg, IP) seizure-threshold test in mice, Fischer et al showed no anticonvulsant effects provided by P2X 7 antagonism using four antagonists (JNJ47965567, AFC5128, BBG, and tanshinone IIA sulfonate).…”
Section: Targeting Of P2x Receptors During Seizures and Epilepsymentioning
confidence: 98%
“…In turn, adenosine generated by the ectonucleotidases, such as NTPDases, NPPases, and alkaline, phosphatase activate P1 (G protein-coupled) receptors as a result of the nucleotide hydrolysis (Fig. 1 ) [ 33 36 ].
Fig.
…”
Section: Possible Link Between Covid-19 Hyper-activated P2x7 Receptor...mentioning
confidence: 99%
“…Purinergic signaling, characterized as a complex regulatory system governed by purine nucleotides such as ATP and nucleosides, is involved in many critical processes of brain development, such as cell proliferation and differentiation, neuron-glia communication, neurotransmitter modulation and inflammatory processes ( Rodrigues et al, 2019 ). In animal models of NE, inflammatory signaling is enhanced in conjunction with upregulation of purine receptors, which can be targeted therapeutically to reduce pathology ( Rodriguez-Alvarez et al, 2017 ; Menendez Mendez et al, 2020 ). Normally, purine signaling molecules (e.g., ATP, adenosine) have relatively low extracellular concentrations, and are also actively released following cellular stress such as inflammation and hypoxia ( Takahashi et al, 2010 ; Thauerer et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%